Enhancing the use of pain assessment at emergency department: a best practice implementation project. (11th September 2022) - Ubierna-Prieto, Joana Aintzane; Ballesteros-Peña, Sendoa; Casbas, Mayte Moreno; Klugarová, Jitka; Klugar, Miloslav
ABSTRACT: Objectives: The main aim of the best practice implementation project was to enhance the use of pain assessment and the compliance with evidence-based criteria regarding pain assessment among incoming patients to emergency department. Introduction: Adequate approaches to pain assessment and documentation have been demonstrated beneficial for emergency department patients. Evidence-based recommendations establish a focus on education about the implications for evaluating and recording pain in order to improve outcome strategies and quality of care. Methods: The implementation project was undertaken in the emergency department following JBI Implementation framework in order to seek whether pain assessment was taken and registered as per protocols. Random selection for 100 anonymized emergency department admission episodes, which had to meet the specified inclusion criteria, was carried out. Results: The baseline audit showed low compliance in criterion 3 (C3) 'Pain was documented in each assessment' (6%), C4 'Pain was assessed after treatment' (9%) and C5 'Pain was assessed prior to discharge' (10%). In the follow-up audit, noticeable improvement was shown for four of the criteria; C3 (14%), C4 (22%) and for C5 (41%). C1 'Pain was assessed in a timely manner' improved from 81% up to 95%. C2 'Use of a validated scoring tool' had a compliance of 100% as the hospital's assessing system default has NRS-11 scale set up. Conclusion: We performed an audit of pain assessment documentation. Enhancing the use of pain assessment among emergency department nurses by means of specific training emphasizing the importance of documentation showed a positive impact on practice. Follow-up audit results justify the continuity of the implemented strategies.